Efecto de inclusión de plectranthus amboinicus en el alimento de pollos broiler sobre la inmunidad. - Peñaloza Marchena, Andres Gerardo; Sanchez Quinche Angel Roberto (Machala : Universidad Técnica de Machala, 2022)
The present investigative work was carried out in the facilities located at the "Santa Inés" Farm located in the Faculty of Agricultural Sciences belonging to the Technical University of Machala. The objective that was raised for this research was to evaluate the effect of the inclusion of dehydrated Plectranthus amboinicus in the balanced feed of Cobb 500 Broiler chickens on immunity. For the execution of the experimental work, 240 chickens of the Cobb 500 line were acquired; mixed, the same ones that were distributed, applying a completely random design (DCA) in metal mesh cages, whose management was carried out under strict biosafety standards established by the university entity and standards of good practices related to poultry farming, with the purpose to beneficially adapt the environment both for the birds and for the project operators. A basic vaccination plan was managed according to the locality, which consisted of the administration of vaccines for Gumboro intermediate strain and New Castle strain La Sota. The balanced feed was made with raw materials acquired through the company "BALMAR". The chickens were distributed in 6 experimental groups, with 4 replicates each, even with 10 chickens per cage. To the first treatment (T1 or control) the growth promoting antibiotic was added, in the second (T2) the growth promoting antibiotic was replaced by the dehydrated leaf of P. amboinicus in the balanced 0.25%, in treatments T3, T4 and T5, the inclusion of P. amboinicus, was 0.50%, 0.75%, 1%, respectively and for T6 dehydrated stem was included at 0.10%. The variables evaluated were: antemortem weight (g), spleen weight (g), bursa weight (g), number of Peyer's patches (n), number of bursa folds (n), spleen morphometric index ( %) and morphometric index of the Bursa (%). On day 35, the birds were sacrificed, for which a male and a female were randomly chosen per experimental unit, obtaining a total of 48 animals, from which the intestines, spleen and bursa were extracted to perform the immunological analysis. . For the weighing of the chickens in the experiment, a gram scale was used with a margin of error of ±1g; CAMRY brand. In the statistical analysis of data, an ANOVA analysis was carried out for one factor. All study variables were analyzed using Statgraphics Centurión XV.I.® (statistical program). In the same way, Fisher's (LSD) multiple comparison procedure was performed to establish the difference and its confidence intervals at a 95.0% level. The results obtained in this study showed that the inclusion in the balanced food of the dehydrated stems and leaves of P. amboinicus in the balanced food supplied to Cobb 500 chickens, does not show a negative or positive effect regarding the immunological factor, Similarly, it is not shown that the first treatment containing growth promoting antibiotic is superior to the other treatments in this parameter studied.
El presente trabajo investigativo fue realizado en las instalaciones ubicadas a la Granja “Santa Inés” situada en la Facultad de Ciencias Agropecuarias perteneciente a la Universidad Técnica de Machala. El objetivo que se planteó para esta investigación fue el de evaluar el efecto de la inclusión de deshidratado de Plectranthus amboinicus en el alimento balanceado de pollos Cobb 500 Broiler sobre la inmunidad. Para la ejecución del trabajo experimental se adquirieron 240 pollos de la línea Cobb 500; mixtos, los mismos que fueron distribuidos, aplicando un diseño completamente al azar (DCA) en jaulas de malla metálica, cuyo manejo se realizó bajo estrictas normas de bioseguridad establecidas por la entidad universitaria y normas de buenas prácticas relacionadas a la avicultura, con la finalidad de adecuar beneficiosamente el ambiente tanto para las aves como para los operadores del proyecto. Se manejó un plan vacunal básico en función a la localidad, mismo que consistía en la administración de vacunas para Gumboro cepa intermedia y New Castle cepa La Sota. El alimento balanceado fue elaborado con materias primas adquiridas mediante la empresa “BALMAR”. Los pollos fueron distribuidos en 6 grupos experimentales, con 4 réplicas cada uno, mismo que contaban con 10 pollos por jaula. Al primero tratamiento (T1 o control) se añadió el antibiótico promotor de crecimiento, en el segundo (T2) se reemplazó el antibiótico promotor de crecimiento por el deshidratado de hoja de P. amboinicus en el balanceado al 0.25 %, en los tratamientos T3, T4 y T5, la inclusión de P. amboinicus, fue de 0.50 %, 0.75 %, 1 %, respectivamente y para el T6 se incluyó tallo deshidrato a 0.10%. Las variables evaluadas fueron: Peso antemortem (g), Peso del bazo (g), Peso de la Bursa (g), número de placas de Peyer (n), número de pliegues de la Bursa (n), índice morfométrico del Bazo (%) e índice morfométrico de la Bursa (%). El día 35 se realizó el sacrificio de las aves, para lo cual se escogieron al azar un macho y una hembra por Unidad experimental obteniendo un total de 48 animales, de los cuales se extrajo, los intestinos, bazo y Bursa para realizar el análisis inmunológico. Para el pesaje de los pollos del experimento se empleó una balanza gramera con un margen de error de ±1g; marca CAMRY. En el análisis estadístico de datos se ejecutó un análisis ANOVA para un factor. Todas las variables de estudio se analizaron mediante el empleo de Statgraphics Centurión XV.I.® (programa estadístico). De la misma forma, se realizó el procedimiento para comparación múltiple de (LSD) de Fisher, para establecer la diferencia y sus intervalos de confianza con un nivel del 95.0%. Los resultados que se obtuvieron en este estudio mostraron que la inclusión en el alimento balanceado del deshidratado de tallos y hojas de P. amboinicus en el alimento balanceado suministrado a pollos Cobb 500, no muestra efecto negativo ni positivo en lo que compete al factor inmunológico, de igual manera, no se demuestra que el primero tratamiento que contenía antibiótico promotor de crecimiento, sea superior a los demás tratamientos en este parámetro estudiado.
Keywords: PARÁMETROS; FACTOR INMUNOLÓGICO; PROMOTOR DE CRECIMIENTO; TRATAMIENTOS